Concrete cover characterisation using dynamic acousto-elastic testing and Rayleigh waves. (1st July 2016) - Vu, Quang Anh; Garnier, Vincent; Chaix, Jean François; Payan, Cédric; Lott, Martin; Eiras, Jesus N.
Highlights: Dynamic acousto-elastic testing by using Rayleigh waves as probe wave and the first bending mode excitation as pump wave. Nonlinear dynamic acousto-elastic behaviour of concrete. High relative variation of nonlinear parameters for assessment of thermally damage concrete and carbonated concrete. The method opens up new possibilities for in situ measurement. Abstract: This paper presents the application of surface Rayleigh waves in nonlinear dynamic acousto-elastic testing for the nondestructive evaluation of the concrete cover. Numerous physical phenomena, such as conditioning and slow dynamics, characterising the dynamic non-classical nonlinear elastic behaviour of many types of micro-heterogeneous solids, were observed in concrete. Rayleigh waves were used as probing waves to evaluate the effect of local property changes in a concrete cover. The proposed method was validated for two typical problems of concrete durability, in a case of thermal damage – distributed micro-damage – and in a case of carbonation – surface problem with determination of the carbonation depth. In both cases, the results showed that the relative variation as a function of material changes of the nonlinear parameters was much higher than that of the ultrasonic pulse velocity.